Analisis Pengaruh Faktor-faktor Pengembangan Sumber Daya Manusia terhadap Kinerja Pegawai Kantor Bapeda Kabupaten Yapen Waropen - Fonataba, Sony B (Universitas Brawijaya, Indonesia, 2008)
The aim of this research are analyzing any influencing factors as such Human Resources Development, which it's containing training, educational and maintenance for staff, which purposed to the performance of employment. Second analyzed Human Resources Development factors which have influenced dominant into performance of employment. With Regression of Linier Multiple Analyzing, Multiple Correlation and so Partial Correlation gained from research result as such below that Human Resources Development factor including staff training, staff education and staff maintenance having general influencing into staff performances for Kantor BAPEDA Kabupaten Yapen Waropen. It proved from analyzed result of Multiple Correlation and F test through F-sum largest than F-table. Meanwhile deeply relation between staff performance and Human Resources Development showed R. That staff maintenance, which one of factor of Human Resources Development have dominated influenced into staff performance. Its showing through analyzed to Linier Regression, Partial Correlation, t test and r2, where variable od staff maintenace obtaining regression value, partial correlation, t test and r2 that largest among another independent variable (training and maintenance staffing).